Correction to: A randomized, open-label, adaptive, proof-of-concept clinical trial of modulation of host thromboinflammatory response in patients with COVID-19: the DAWn-Antico study - T. Vanassche (Trials, 2020)
An amendment to this paper has been published and can be accessed via the original article.